The philosophy of contemporary industrial design in the light of the fourth industrial revolution - REHAB MAHMOUD ABDELAZIM ABDALLAH (Journal of Architecture, Art & Humanistic Science, 2020)
The design is linked always to both social and technological forces, which in turn influence the form, nature and implementation of the design and by the fourth industrial revolution a prelude to the philosophy of contemporary industrial design based on contemporary technologies such as 3D printers and the revolution of ultra-fast communications in its various forms such as the Internet of Things and others, contributed to the transition from quantitative production to individual production (more personalized manufacturing). This requires a different way of designing and updating the product where advances in design theory and computer technology provide greater opportunities for new products and systems for rapid success without added cost, and provides the opportunity to pay attention to the development of the model as one of the satisfactory solutions for product development and ensuring its competitive ness and speed, and the use of new computer-supported design tools to deal with a full range of planning and design requirements. Fundamental changes must be made to understand how to take full advantage of new technologies as much of the success of the global economy in the third millennium will depend on the ability to find a way to share developments in design technology and market knowledge.In order to contribute to the consolidation of this concept, a study should be presented on the impact of high-speed market requirements on the process of product modernization and utilization of the use of manufacturing technology in line with contemporary requirements taking into account the contribution of design education in building the knowledge of the learner's knowledge of the requirements of the development and transformation of production from quantum to the production of fast and flexible batches covering the demand for it in limited quantities by issuing a new model of the product, in view of reducing the cost in order to meet the urgent need of markets for renewal in record time. The study plan on the use of research and the in-kind approach provided a proposal for how industrial design contributes in the light of the data of the fourth industrial revolution through how to guide and use contemporary possibilities to design the fastest and cheapest model of products and services in keeping with the current nature of the market.